Medicine Bottles (1919–1939) found at 15A Užupio Street, Vilnius: Results of the Research and Interpretation of their Contents - Muralis, Vismantas; Šimkutė, Viktorija; Vičkačkaitė, Vida; Žvirblys, Atas (Archaeologia Lituana, 2024)
Archaeological investigation was carried out in the first half of 2022 on the site Užupio g. 15A, which falls within the territory of the Vilnius St. Bartholomew’s Church building complex. During the research it was expected to find cultural layer horizons associated with the church and the cemetery next to it. Although archaeological finds and disturbed graves were discovered during the excavation, the most intriguing finds were collected in recessed structures dating from the first half of the XX century. As many as 69 bottles and vials were collected, most of which were used to store medicines. Four individual fragments with inscriptions were also found. Among the finds above, three bottles were found with preserved contents inside. This article, which is an interdisciplinary collaboration between archaeologists, historians, and chemists, analyses the archaeological and historical context of the mentioned finds, the places of manufacture of the discovered medicine bottles, the results of analyses of the contents found in the bottles, and interpretations of the possible uses of the recovered medicinal substances.